Effects of peanut cultivars and neem oil on the feeding preference, growth and mortality of fall armyworm and velvet bean caterpillar (Lepidoptera: Noctuidae) - Costa, Eduardo Neves [UNESP]; de Souza, Bruno Henrique Sardinha; Eduardo, Wellington Ivo [UNESP]; de Moraes, Renato Franco Oliveira [UNESP]; Ribeiro, Zulene Antonio [UNESP]; Júnior, Arlindo Leal Boiça [UNESP] (Springer Nature, 2022)
The fall armyworm (FAW), Spodoptera frugiperda and the velvet bean caterpillar (VBC), Anticarsia gemmatalis are pests that can cause severe defoliation of peanut plants during any development stage throughout the Americas. This study aimed to evaluate effects of a bioinsecticide, neem oil, and two peanut cultivars on feeding preference, period of development, and mortality of FAW and VBC. Furthermore, wax content was estimated to correlate with peanut resistance. In the laboratory, feeding preference was tested under choice and no-choice assays. First and third instar larvae were released into Petri dishes containing leaves from the cultivars IAC Runner 886 or IAC Caiapó, with or without the application of either 0.15% or 0.30% neem oil. Considering the peanut cultivars, IAC Runner 886 was the least consumed by FAW third-instar larvae, in choice and no-choice tests. Similarly, the cultivar IAC Caiapó was the least consumed by VBC third instar larvae in no-choice test. When neem oil was added to these cultivars, FAW first-instar larvae exhibited feeding deterrence behaviors, whereas third-instar larvae also were deterred by neem oil but in only the free-choice assay. The first instar VBC larvae exhibited feeding deterrence to neem oil in the no-choice assay only. Overall, no larvae subjected to neem oil application completed the larval cycle. This study showed that certain peanut cultivars and neem oil are indeed promising options for managing FAW and VBC and opens the door to further study these options in the field. The relationship between wax content with peanut resistance is discussed.
Keywords: Anticarsia gemmatalis; Arachis hypogaea L; Azadirachta indica A. Juss; Botanical insecticides; Integrated pest management; Spodoptera frugiperda